Assessing the Difference Between the Number of CD3+20+ T Cells by Flowcytometry in Idiopathic Nephrotic Syndrome Patients in Relapse and Remission Period: A Pilot Study: Assessing the Number of CD3+20+ T Cells in Relapse and Remission Period in INS - Marzani, Seyedeh Fatemeh (Journal of Pediatric Nephrology, 2025)
Background and Aim: The pathogenesis of idiopathic nephrotic syndrome (INS) remains unclear. Previously, the INS was assumed a T cell-mediated disease. Cytokines secreted from T helper 2 cells, reduced T regulatories, which led to activation of T effector cells, resulting in the increased permeability of glomerulus and nephrotic syndrome. The remedial influence of B cell depletion by anti-cluster of differentiation marker 20 factors suggests a role of B cells in the pathogenesis of the disease. However, the exact mechanisms of action of these medications are unknown. One of these mechanisms is the effect on CD3-20+ T cells. Methods: A total of 10 patients in relapse of INS and 10 patients in remission were included in this study. The number of CD3-20+ T cells was calculated by flow cytometry in these two groups. Results: In the relapse group, on average, 1.10% of T cells were CD3-20+ cells; in the remission group, the same data was 0.41%. Conclusion: The mean number of CD3-20+ T cells in the remission group was lower than in the relapse group; however, there was no statistical difference between the two groups